2022
DOI: 10.3390/electronics11213483
|View full text |Cite
|
Sign up to set email alerts
|

Digitization and Financial Performance of Banking Sectors Facing COVID-19 Challenges in Central and Eastern European Countries

Abstract: The COVID-19 pandemic deeply impacted not only human wealth but also all segments of the economy as well as the field of technology. Thus, the purpose of this paper was to analyze the effects that the pandemic crisis and digitization have had on the financial performance of banks in Central and Eastern European Union countries (CEEC) during the 2010–2021 period. In order to capture an overview of the financial performance of the banking systems in the 10 CEECs, we used three variables—ROA, ROE and NPL—as refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…A similar study that included samples for a brief post-pandemic period 2020-2021 used ROE and ROA-Return on Assets-to evaluate the bank's performance. It also shows that digitalization helped banks to stay profitable (Doran et al 2022).…”
Section: Ict and Its Relevance For Banks Post-covidmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar study that included samples for a brief post-pandemic period 2020-2021 used ROE and ROA-Return on Assets-to evaluate the bank's performance. It also shows that digitalization helped banks to stay profitable (Doran et al 2022).…”
Section: Ict and Its Relevance For Banks Post-covidmentioning
confidence: 99%
“…Few studies from the pre-COVID-19 period concluded that ICT impacts a bank's profitability, and the bank's size also plays a role. Studies like that of Doran et al (2022) have an overlapping sample that does not compare the pre-COVID-19 and post-COVID-19 performance as a primary objective but as a periodic change.…”
Section: Ict and Its Relevance For Banks Post-covidmentioning
confidence: 99%
“…The conditions imposed by the pandemic have led the population to conduct more transactions through digital platforms, which has accelerated the adoption of banking and financial digitization [35]. This study considered some accounting measures of performance such as the ROA, ROE, and the ratio of Non-Performing Loan Portfolio to Total Portfolio, but as a function of some indicators of technological capabilities, such as the number of ATMs, the number of security certificates, or the use of the internet.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The COVID-19 pandemic caused numerous disruptions in the entire ecosystem, but the ones affecting the economic environment generated various types of crises for economies [39][40][41] and especially businesses [42][43][44], as well as the financial and banking systems [45][46][47][48]. Probably the most consistent approach of economic actors to better face the pandemic has been rethinking organizations to reduce costs, recover revenue streams, rebuild operations, and develop the customer base.…”
Section: Introductionmentioning
confidence: 99%